Molecular mechanisms of ferroptosis and their role in inflammation. (2nd January 2023) - Wang, Feng; He, Jingya; Xing, Ruxiao; Sha, Tong; Sun, Bin
Abstract: Ferroptosis is a type of non-apoptotic cell death, which demonstrates a definite iron-dependent expression pattern and is associated with lipid peroxidation. Glutathione peroxidase 4 (GPX4) is a key regulator of ferroptosis. Ferroptosis is involved in the development and progression of various diseases, such as cancer, tissue ischemia–reperfusion injury, neurological diseases, and respiratory diseases. It has been established previously that ferroptotic cells trigger the innate immune system by releasing inflammation-linked damage-related molecules, and immune cells stimulate the inflammatory response by recognizing the operational mechanism of ferroptosis. Some anti-inflammatory drugs have been shown to inhibit ferroptosis in certain cell models. Conversely, some ferroptosis inhibitors also exert anti-inflammatory effects in certain diseases. The present review evaluated the relationship between ferroptosis and inflammation, as well as the underlying internal mechanism, and provided valuable insights into developing novel treatment strategies for inflammatory diseases and cancer.